Extracellular vesicles from human cardiac progenitor cells inhibit cardiomyocyte apoptosis and improve cardiac function after myocardial infarction. (11th July 2014) - Barile, Lucio; Lionetti, Vincenzo; Cervio, Elisabetta; Matteucci, Marco; Gherghiceanu, Mihaela; Popescu, Laurentiu M.; Torre, Tiziano; Siclari, Francesco; Moccetti, Tiziano; Vassalli, Giuseppe
Abstract: Aims: Recent evidence suggests that cardiac progenitor cells (CPCs) may improve cardiac function after injury. The underlying mechanisms are indirect, but their mediators remain unidentified. Exosomes and other secreted membrane vesicles, hereafter collectively referred to as extracellular vesicles (EVs), act as paracrine signalling mediators. Here, we report that EVs secreted by human CPCs are crucial cardioprotective agents. Methods and results: CPCs were derived from atrial appendage explants from patients who underwent heart valve surgery. CPC-conditioned medium (CM) inhibited apoptosis in mouse HL-1 cardiomyocytic cells, while enhancing tube formation in human umbilical vein endothelial cells. These effects were abrogated by depleting CM of EVs. They were reproduced by EVs secreted by CPCs, but not by those secreted by human dermal fibroblasts. Transmission electron microscopy and nanoparticle tracking analysis showed most EVs to be 30–90 nm in diameter, the size of exosomes, although smaller and larger vesicles were also present. MicroRNAs most highly enriched in EVs secreted by CPCs compared with fibroblasts included miR-210, miR-132, and miR-146a-3p. miR-210 down-regulated its known targets, ephrin A3 and PTP1b, inhibiting apoptosis in cardiomyocytic cells. miR-132 down-regulated its target, RasGAP-p120, enhancing tube formation in endothelial cells. Infarcted hearts injected with EVs from CPCs, but not from fibroblasts, exhibited less cardiomyocyte apoptosis, enhanced angiogenesis, and improved LV ejection fraction (0.8 ± 6.8 vs. −21.3 ± 4.5%; P < 0.05) compared with those injected with control medium. Conclusion: EVs are the active component of the paracrine secretion by human CPCs. As a cell-free approach, EVs could circumvent many of the limitations of cell transplantation.